High intratumoral macrophage content is an adverse prognostic feature in anaplastic large cell lymphoma. Issue 6 (16th April 2014) - Pedersen, Martin B; Danielsen, Allan V; Hamilton‐Dutoit, Stephen J; Bendix, Knud; Nørgaard, Peter; Møller, Michael B; Steiniche, Torben; d'Amore, Francesco
Abstract : Aims: Macrophage infiltration has been associated with prognosis in several cancers, including lymphoma, but has not been assessed systematically in anaplastic large cell lymphoma (ALCL). The aim of the study was to correlate expression of the macrophage‐associated antigens CD68 and CD163 with pre‐therapeutic parameters and outcome in a cohort of treatment‐naive ALCL patients. Methods and results: Pre‐therapeutic tumour specimens from 52 patients with ALCL were included in a tissue microarray. The intratumoral macrophage content was assessed by immunohistochemical staining for CD68 and CD163, and quantified using digital image analysis. Anaplastic lymphoma kinase (ALK)‐positive patients were significantly younger and had a favourable outcome compared with ALK‐negative ALCL patients (median age: 42 versus 59 years; P = 0.008). However, ALK expression was not a significant predictor when adjusting for age. Although classical risk factors were distributed evenly between the compared groups, high intratumoral content of CD68 and/or CD163 correlated with poor outcome, in both univariate and multivariate analyses. High intratumoral CD163 content showed the strongest adverse association with both overall and progression‐free survival in ALK‐negative patients ( P < 0.001). Conclusions: A high content of intratumoral CD68‐ and/or CD163‐positive macrophages correlates with an adverse outcome in ALK‐negative ALCL.